2016
DOI: 10.18203/2394-6040.ijcmph20164271
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of menstrual health among school going adolescent girls of urban slums of Berhampur, Odisha, India: a cross-sectional study

Abstract: Background: Menarche is a significant milestone in the developmental journey of an adolescent girl about which she should be aware so that she can manage it properly. Poor personal hygiene and unhealthy menstrual practices give rise to repeated reproductive tract infections (RTIs). The Objectives were to assess the knowledge and perception regarding menarche; to study various problems related to menstruation and to evaluate various practices to manage menstruation with special emphasis on hygiene. Methods: Fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…In a study, clothes were reused by 73% of them. [ 26 ] In India, most schools lack the provision of dustbins and hand soaps. Toilets are dirt with doors broken.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study, clothes were reused by 73% of them. [ 26 ] In India, most schools lack the provision of dustbins and hand soaps. Toilets are dirt with doors broken.…”
Section: Methodsmentioning
confidence: 99%
“…[ 27 ] A study showed only 42% changed their pads/clothes in the school due to the non-availability of dustbins and soaps. [ 26 28 ]…”
Section: Methodsmentioning
confidence: 99%